Staying competitive by using R&D to increase productivity - Abd Razak, Dzulkifli (2003)
FOR the Malaysian scientific community, among the many parting gestures at tributed to Tun Dr Mahathir Mohamad, his suggestion to boost rational research and development (R&D), is perhaps the most exciting. Indeed, his 2004 Budget presentation won the hearts of many scientists and researchers when he proposed that the rules and regulations governing universities and the use of government funds for R&D ought to be relaxed (NST, Sept 6). This will not only give researchers more autonomy to work creatively and independently, but it can also assist in promoting the economic and social growth of the country. After all, appropriate R&D can produce relevant technology that could spur productivity and ultimately improve quality of life. This is especially so if at the same time universityindustrycommunity cooperation is facilitated.